CYP2D6 genotyping analysis and functional characterization of novel allelic variants in a Ni-Vanuatu and Kenyan population by assessing dextromethorphan O-demethylation activity. Issue 1 (February 2020) - Gutiérrez Rico, Evelyn Marie; Kikuchi, Aoi; Saito, Takahiro; Kumondai, Masaki; Hishinuma, Eiji; Kaneko, Akira; Chan, Chim Wai; Gitaka, Jesse; Nakayoshi, Tomoki; Oda, Akifumi; Saito, Sakae; Hirasawa, Noriyasu; et al.
Abstract: While CYP2D6 allele and phenotype frequencies have been extensively studied, currently, very little ethnically specific data is available regarding the East African and South Pacific region, including Kenya and Vanuatu. The absence of information regarding gene polymorphisms and their resulting clinical effects in these populations may hinder treatment strategies and patient outcome. Given the scarceness of CYP2D6 related data in these populations, the purpose of this study was to perform a pharmacogenomic analysis of the Kenyan and Ni-Vanuatu population and ultimately characterize the enzymatic properties of eight novel CYP2D6 variant proteins expressed in 293FT cells in vitro using dextromethorphan as a substrate. Our study revealed a prevalence of functional alleles in both populations a low frequency for decreased function defining genotypes in the Ni-Vanuatu population, with approximately 36% of our Kenyan subjects presenting substrate-dependent decreased function alleles. Additionally, 6 variants (P171L, G306R, V402L, K1, K2, and K3) showed significantly reduced intrinsic clearance compared to wild-type CYP2D6.1. Our findings aid in efforts to bridge the gap between pharmacogenomic analysis and clinical application, by providing useful information in the development of ethnic-specific strategies as well as stressing the importance of population-specific genotyping when conducting multi-regional clinical trials and designing therapeutic strategies. Graphical abstract: Image 1